2000
DOI: 10.1007/s101620010010
|View full text |Cite
|
Sign up to set email alerts
|

Helical Structure of Hair Cell Stereocilia Tip Links In the Chinchilla Cochlea

Abstract: Outer-hair-cell stereocilia tip-link structure in the chinchilla cochlea was studied by transmission electron microscopy using tannic acid and Ruthenium red/ Alcian blue histochemical procedures. Tannic acid and Ruthenium red/Alcian blue treatments showed the tip link as a compact strand of filaments 9-12 nm thick. Fourier analysis of tip-link images showed that the strand is a three-start helical bundle of fine, coiled filaments which had an axial period of 22.5+/-1.5 nm. Each of three coiled filaments in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 9 publications
(1 reference statement)
2
27
0
Order By: Relevance
“…This behavior suggests a well-defined, rather stiff conformation of the basal-link protein. twisted around each other (Tsuprun et al 2004), threedimensional analysis showed that the filaments are separated. Filaments appear to be grouped and insert into only the thicker membrane portions of the kinociliary bulb (Fig.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations
“…This behavior suggests a well-defined, rather stiff conformation of the basal-link protein. twisted around each other (Tsuprun et al 2004), threedimensional analysis showed that the filaments are separated. Filaments appear to be grouped and insert into only the thicker membrane portions of the kinociliary bulb (Fig.…”
Section: Figmentioning
confidence: 99%
“…Connections of the second type, kinociliary links, then transmit these stimuli to the five longest stereocilia (Hillman and Lewis 1971). Fourier analysis of electron-microscopic images suggests that kinociliary links constitute an array of several dozen fine strands that are arranged in a coiled-coil conformation (Csukas et al 1987;Tsuprun et al 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the tip-link model for transduction, the tip links act as gating springs for mechanically sensitive ion channels (Hudspeth 1989;Pickles and Corey 1992). Results from electron microscopy recently showed that the tip link consists of many globular protein structures periodically arranged into two or three filaments with a helical symmetry (Kachar et al 2000;Tsuprun and Santi 2000). These globular structures may correspond to individual protein subunits or may represent repeating identical domains of one polypeptide (Tsuprun and Santi 2000).…”
mentioning
confidence: 99%